Evaluating the Importance of Ecosystem Services in University Campus - Giao Thanh Nguyen; Dan Hoang Truong (Civil Engineering Journal, 2024)
University campuses provide a variety of ecosystem services (ES) that play an important role in both physical and mental benefits for students. However, the importance and actual service performance of ES in universities were not clearly perceived in Vietnam. This study was conducted to fill these gaps with the objectives of (1) assessing students' perceptions of the importance of ecosystem services on their university campus and (2) assessing students' satisfaction with these ecosystem services. Using the interview method, the study collected research data from 210 students at Can Tho University (CTU), a large university in Vietnam. The results of the study have confirmed the importance of ecosystem services such as trees, lawns, water bodies, and buildings on CTU's campus. With modern design, buildings play an important role in creating space to organize formal classes, self-study, and group work for students. Green spaces not only improve air temperature and bring high aesthetic value, but they are also habitats for many species of animals and plants. Most students were very satisfied with the ES provided by the CTU's campus. However, the functions of the grass and water bodies ecosystem need to be improved, as the student satisfaction with these ES was significantly lower than the value they expected. The results of analyzing the importance and satisfaction of ES will be a useful basis for making decisions on planning and developing ecosystems. This is a new research direction in Vietnam that needs continued research and application. Doi: 10.28991/CEJ-2024-010-01-015 Full Text: PDF